Teknik dan Instrumen Asesmen Ranah Kognitif - Putri Wulandari (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
Assessment seeks to determine whether educational goals are achieved or not, so that evaluation has a very large role in the world of education. Effective and efficient evaluations are carried out continuously and comprehensively, it is hoped that educators can get a complete picture of the achievements and progress of the process and learning outcomes achieved by students. Each subject emphasizes continuous evaluation, referring to comprehensive goals and results. Among the domains of differentiation in education is the cognitive domain. Cognitive assessment is an activity carried out to measure students' mastery of knowledge. The assessment of cognitive aspects is carried out through stages: preparing an assessment plan, developing an assessment instrument, carrying out the assessment, utilizing the assessment results, and reporting the assessment results in the form of numbers on a scale of 0-100 and description.